2005
DOI: 10.1111/j.1742-4658.2005.04571.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α‐synuclein aggregation and synergistic toxicity with protein tau in yeast

Abstract: A yeast model was generated to study the mechanisms and phenotypical repercussions of expression of α‐synuclein as well as the coexpression of protein tau. The data show that aggregation of α‐synuclein is a nucleation–elongation process initiated at the plasma membrane. Aggregation is consistently enhanced by dimethyl sulfoxide, which is known to increase the level of phospholipids and membranes in yeast cells. Aggregation of α‐synuclein was also triggered by treatment of the yeast cells with ferrous ions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 71 publications
7
88
1
2
Order By: Relevance
“…Consistent with our previous findings (30), we found that the relative amount of synaptosomal ␣-syn in the membrane-bound and cytosolic fractions was similar for WT, A30P and A53T ␣-syn. Experiments in yeast have suggested that A30P ␣-syn has a lower membrane binding capacity than WT and A53T ␣-syn (41,42). However, we have previously shown that cytosolic factors expressed in brain, which yeast may lack, influence the membrane binding ability of recombinant ␣-syn and can indeed increase the binding capacity of A30P ␣-syn (11).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous findings (30), we found that the relative amount of synaptosomal ␣-syn in the membrane-bound and cytosolic fractions was similar for WT, A30P and A53T ␣-syn. Experiments in yeast have suggested that A30P ␣-syn has a lower membrane binding capacity than WT and A53T ␣-syn (41,42). However, we have previously shown that cytosolic factors expressed in brain, which yeast may lack, influence the membrane binding ability of recombinant ␣-syn and can indeed increase the binding capacity of A30P ␣-syn (11).…”
Section: Discussionmentioning
confidence: 99%
“…As shown previously (Outeiro and Lindquist, 2003;Zabrocki et al, 2005;Dixon et al, 2005), ␣-syn-EGFP prominently localized to plasma membranes and formed cytoplasmic accumulations, whereas EGFP alone showed a diffuse cytoplasmic distribution ( Figures 1A and 2A). The ␣-syn clusters/accumulations varied considerably in size, and many of the smaller ones appeared to be associated with the cell cortex, whereas larger accumulations were sometimes completely localized to the cytoplasm, suggesting that they may form initially at the plasma membrane or the ER, which underlies the plasma membrane in yeast ( Figure 1D).…”
Section: ␣-Synuclein Accumulation In the Cytoplasm Of S Cerevisiae Imentioning
confidence: 51%
“…These cells produced twice the percentage of cytoplasmic ␣-syn accumulations as the nonintegrated strain (Supplementary Figure 2). The number of cells with ␣-syn accumulations was further enhanced to ϳ70% by treatment of these yeast with 5% DMSO (Zabrocki et al, 2005). Surprisingly, EM analyses of the cells expressing ␣-syn-EGFP did not reveal filamentous ␣-syn-or LB-like structures.…”
mentioning
confidence: 97%
“…Soluble ␣Syn can be targeted to the 26 S proteasome for degradation (31)(32)(33)(34) or can be degraded by the autophagy-lysosomal pathway (33)(34)(35)(36). The budding yeast Saccharomyces cerevisiae has been extensively used as a powerful system to study the basic molecular mechanisms involved in ␣Syn-mediated cytotoxicity (37)(38)(39)(40). We showed that aggregate clearance of ␣Syn depends mainly on the autophagy pathway (38).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%